Marvell as Miltonist - JAMES GRANTHAM TURNER (Marvell Studies, 2024)
Marvell’s commendations of Milton prove him a perceptive critic of the Latin prose and the epic verse. Not merely summarizing the content or intoning conventional praise, he invents a structural or architectonic mode of reading, articulates a subjective and emotional reader-response, connects Milton and the sublime for the first time, and evokes ancient models particularly significant for Milton. The 1654 letter comparing Milton’s Defensio Secunda to Trajan’s Column, turning and simultaneously rising to a higher “Scale,” endorses Milton’s own claim that it is a canonical work of epic stature. Marvell’s architectural imagery, expanded from Milton’s own Areopagitica, applies also to Cromwell’s use of dissidents as cross-bracing, “Fastening the Contignation which they thwart.” The commendatory poem to the 1674 edition of Paradise Lost again incorporates what seems at first to “thwart” the whole project. Here the significant intertext is De Rerum Natura by the notorious “atheist” Lucretius – the “strong” but dangerous poet who had already done what Marvell fears Milton might do: “ruin the sacred Truths.” Lucretian allusion expands to define the emotional and aesthetic impact of Paradise Lost, anticipating the “terror without danger” at the core of Burke’s Sublime. (The key-word “sublime” becomes the end-rhyme of Marvell’s penultimate line.) Lucretius, awestruck by his philosophical mentor Epicurus ,is “seized by divina voluptas and horror”; Marvell, yielding to the contradictory “gravity and ease” of Milton’s poetry but also asserting his own aesthetic, exclaims that “at once delight and horror on us seize.”